Expression of CK 19 as a biomarker in early detection of oral squamous cell carcinoma - Rajeswari, Parvathy (J Oral Maxillofac Pathol, 2020)
BACKGROUND: Increased mortality in oral squamous cell carcinoma (OSCC) had been attributed to delay in diagnosis. Lack of a specific marker to assess the malignant potential of premalignant lesions is thought to be one of the reasons for late detection. Expression of Cytokeratin 19, which is widely used as an odontogenic epithelial marker had been reported in OSCC. Downregulation of CK 19 expression plays an important role in terminal differentiation of superficial squamous cell and increased expression in various epithelial malignancies has been suggested to be an indicator of malignant change. AIMS AND OBJECTIVES: To assess the role of CK19 as a potential marker in predicting malignant transformation in oral precancerous lesions and as a prognostic marker in OSCC. MATERIALS AND METHODS: Study population consisted of ten samples each of normal oral mucosa, epithelial hyperplasia, varying grades of both oral epithelial dysplasias and OSCC. The tissue sections were subjected to immunohistochemical staining for the marker cytokeratin 19. RESULTS: An increased expression of CK19 was noted in oral epithelial hyperplasia, severe dysplasia and in superficial epithelium at the invading front in OSCC. In mild and moderate dysplasias, CK19 expression was lower than the normal mucosa. In oral squamous cell carcinoma, the expression of CK19 was restricted to either a few islands or a few cells within the islands, resulting in a lesser expression than the normal epithelium. The malignant epithelial islands in the superficial connective tissue stroma were showing greater expression than the deeper islands. The epithelial cells associated with formation of keratin pearls were found to be showing more expression than those with infrequent keratin pearls. CONCLUSION: The study suggests that malignant transformation of epithelium can be predicted based on the increased expression of CK19. But it should be done with caution as a similar increased expression may also be noticed in presence of inflammation.